Psychology : themes and variations - WEITEN, Wayne (Pacific Grove : Books/Cole Publishing Co., 1997)
Emphasizes ideas instead of isolated facts and shows how research and application work in harmony. The text challenges students to grapple with the big issues and tough questions, while at the same time helping them master the basic concepts of psychology.
Includes bibliography and index
Keywords: Psychology Textbooks, Psychology, Psychologie